Diversity and conservation status of the Ichthyofauna of the Río Lacantún basin in the Biosphere Reserve Montes Azules, Chiapas, México - Lozano-Vilano, M. L; García-Ramírez, M. E; Contreras-Balderas, S.; Ramírez-Martínez, Y C. (Zootaxa, 2007)
The Biosphere Reserve Montes Azules (RBMA), located in the Mexican southeastern state of Chiapas, is the most important floral and faunal reserve in México and Mesoamerica, The reserve contains the largest and best preserved forests in the region, as well as the few remaining pristine rivers. The primary objective of this paper is to update the fish diversity along the southern part of this important reserve, based on material collected during eight expeditions carried out from 2004 to 2006. Fish samples were obtained from 20 localities, of which seven were inside the protected natural area. A total of 8, 977 specimens were collected, representing 55 species (including one unidentified and three aliens) in 41 genera and 23 families. This paper adds 9 more species to the regional fish fauna, one of them are exotic. According to their zoogeographic origin, three are Nearctic, 32 are Neotropical, and 17 are in other groups; ecologically, nine species are of primary derivation, 26 are Secondary, and 17 are Peripheral or Vicarious, according to Myers’ (1938) classification based on historical salinity tolerance. The most diverse fish families were the Cichlidae and Poeciliidae, with 15 and eight species, respectively. Compared to other Mexican hydrological regions, the study area contains a fish fauna that is still well preserved in terms of diversity, but ecological damage is due to humans living adjacent to the reserve. If this situation continues unchecked, it could threaten the survival of some species.